Inspection of social services in Sweden: a comparative analysis of the use and adjustment of standards. Issue 2 (3rd May 2016) - Hämberg, Eva; Sedelius, Thomas
Abstract: State supervision – based on different kinds of standard-setting components and sanctions – has increasingly been regarded as one of the most important safeguards for promoting the quality of, and public confidence in state-regulated activities. In several countries, there have been a number of organizational changes and changes in instrument design aiming to improve the effectiveness of supervision within the social service sector. However, little attention has been given to the impact of different standard designs on supervision. The aim of this study is to empirically contribute to a broadened understanding of how standards in supervision are designed, and what implications the design has on the effectiveness of social service supervision. In this study, we employ a systematic and comparative analysis of the content (in terms of input, process, output and outcome aspects) and precision (low, medium and high) of 186 standards used in completed state supervisory decisions within two different types of social work: Investigation, Assessment and Decision-Making (IAD); and Treatment Work (TW) in Sweden during 2012. Contrary to expectations based on a supervision system ideal, the findings show that outcome aspects, i.e. factors related to long-term client effects, are rarely used and not more so in TW than in IAD supervision. In addition, the analysis of standard precision indicates that supervision of TW cannot identify deficiencies related to complex and subjectively experienced aspects to any greater extent than IAD. The overall results indicate that the supervisory instrument is primarily adapted to IAD-supervision, but is less suited to optimally covering central aspects of TW.